An Efficient Heuristic Solution to the Single-Facility Euclidean Location Problem - Kuo, Ching-Chung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2010)
It is well known in location theory that the modified gradient procedure (MGP) is called for to solve the Euclidean mini-sum single facility location problem (MSSFLP). Since it is often tedious to implement the MGP, some researchers have proposed the use of the center of gravity (COG) as an approximation to the optimal solution to the Euclidean MSSFLP to reduce the computational efforts. They argue that, aside from the advantage of being easy to calculate, the COG usually results in a transportation cost that is close to the true minimum albeit no evidence is provided. The main thrust of this paper is to conduct a simulation experiment to empirically substantiate the claim. In addition, data collected from the study is subject to regression analysis to identify the key factors affecting the effectiveness of the COG as a substitute for the MGP-based optimal solution to the Euclidean MSSFLP in practical applications.